Inversión extranjera directa crecimiento económico y spillovers en los países menos desarrollados miembros del APEC - Cuadra, Gabriela (2003)
The main objective of this research is to understand the effect of foreign direct investment (FDI) on the growth of the less developed countries members of APEC, considering the transfer and diffusion of technology between the most developed countries and the least developed countries as the most important source. important of the overflow of knowledge. To this end, an endogenous growth model is developed - with two countries and three sectors - that allows us to understand the relationships behind FDI and its consequent effects. Then, the model is implemented by estimating one of the main equations with the Panel Data technique. It is found that, indeed, FDI causes a positive impact on the growth rate of less developed countries and that this impact depends, to a large extent, on the stock of human capital existing in the host country. This effect is significant since the nineties, a period during which structural reforms are implemented or accentuated in many of the countries included in the study.